ANALISIS KETERAMPILAN BERBICARA DALAM PEMBELAJARAN KURIKULUM MERDEKA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SD UNGGULAN MUSLIMAT NU KUDUS - Nabila Mustafafi; Sri Utaminingsih; Fitriyah Amaliyah (STKIP Subang, 2023)
ABSTRACT The Covid-19 pandemic changed the curriculum to learning, methods, namely online learning (online) which after running there is Learning Loss. Overcoming this, the Ministry of Education and Culture establishes an independent curriculum as a recovery, in which it strengthens the profile of Pancasila students as the embodiment of Indonesian student who are globally competent and have 21st century skills, namely 4C skills creativity, critical thinking, communication, collaboration. In society, communication is important as a daily identity and in elementary schools it requires attention to learning speaking skills through Indonesian language subjects. The purpose of this study to describe the speaking skills in storytelling in the independent curriculum learning Indonesian language class IV Al Maraghy and the factors that influence the speaking skills in storytelling in the independent curriculum learning with qualitative research methods. The research data used observation, interviews, and documentation at Unggulan Muslimat Elementary School. The result showed that speaking skills in storytelling in Class IV Al Maraghy in the independent curriculum learning had different skill, namely high, medium, and low abilities. The factors that influence speaking skills in storytelling are internal factors such as motivational factors, and self-confidence factors. While external factors such as mother tongue factors, environmental factors, and teachers factors.